Granville Sharp correspondence - Sharp, Granville, 1735-1813.
ALS (1785 January 19) from Sharp to the Rev. Mr. Witton in Northumberland, England, and ALS (1806 March 4) from Sharp to William Lodge, merchant in New York, N.Y., both relating to deeds and other legal matters.
British philanthropist and abolitionist.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Lodge, William -- Correspondence; Witton, -- Rev. Mr. -- Correspondence; Deeds -- England -- Northumberland; Deeds -- New York (State) -- New York; Abolitionists; Philanthropists